Immediate Pain Relief in Adhesive Capsulitis by Acupuncture—A Randomized Controlled Double-Blinded Study. Issue 11 (20th March 2017) - Schröder, Sven; Meyer-Hamme, Gesa; Friedemann, Thomas; Kirch, Sebastian; Hauck, Michael; Plaetke, Rosemarie; Friedrichs, Sunja; Gulati, Amit; Briem, Daniel
Abstract: Objective: Primary adhesive capsulitis (AC), or frozen shoulder, is an insidious and idiopathic disease. Severe pain is predominant in the first two of the three stages of the condition, which can last up to 21 months. Design, Setting, and Subjects: Sixty volunteers with primary AC were randomly assigned to acupuncture with press tack needles compared with press tack placebos in a patient- and observer-blinded placebo-controlled study. The participants were subsequently offered classical needle acupuncture in an open follow-up clinical application. Thirty-four volunteers received conservative therapy, including 10 classical needle acupuncture treatments over 10 weeks, 13 volunteers received conservative therapy without classical needle acupuncture. All subjects agreed to follow-up after one year. Methods: Acupuncture treatment was performed using a specific distal needling concept, using reflex areas on distant extremities avoiding local treatment. Results: An immediate improvement of 3.3 ± 3.2 points in Constant-Murley Shoulder Score (CMS) pain subscore was seen in the press tack needles group and of 1.6 ± 2.8 points in the press tack placebos group ( P <0.02). Conservative therapy including classical needle acupuncture significantly improved the pain subscore within 14.9 ± 15.9 weeks compared with 30.9 ± 15.8 weeks with only conservative therapy ( P < 0.001). Conclusion: The efficiency of distal needling acupuncture on immediate pain reduction was demonstrated in patients with AC and confirmed the applicability of press tack needles and press tack placebos for double-blind studies in acupuncture. Subsequent clinical application observation proved that results obtained with press tack needles/press tack placebos can be transferred to classical needle acupuncture. Integrating acupuncture with conservative therapy showed superior effectiveness with respect to the time course of the recovery process in AC compared with conservative therapy alone.